The effect of the Wnt pathway on the osteogenic differentiation of periodontal ligament stem cells in different environments - Qi Su; Fengqiong Huang; XiuLei Fang; Qiang Lin (PeerJ)
Alveolar bone defects have always been an urgent problem in the oral cavity. For some patients with periodontal disease or undergoing orthodontic treatment or implant restoration, alveolar bone defects can greatly inconvenience clinical diagnosis and treatment. Periodontal ligament stem cells (PDLSCs) are considered a promising source for stem cell therapy due to their high osteogenic differentiation capability. The osteogenic differentiation of PDLSCs is influenced by various cytokines mediating signaling pathways, as well as a range of biochemical, physical, and chemical factors. Different environments typically impact the Wnt signaling pathway and consequently affect the osteogenic differentiation of PDLSCs. Understanding the effects of the Wnt signaling pathway on the osteogenic differentiation of periodontal ligament stem cells in various environments contributes to addressing the diverse clinical scenarios encountered in the oral environment. This knowledge aids in influencing the pathway through bioengineering or the development of novel materials, thereby enhancing the osteogenic potential of stem cells and providing new diagnostic and therapeutic strategies for clinical practice.